Identifikasi Kegiatan Pemberdayaan Masyarakat Untuk Pembangunan Kesejahteraan - Utan Sahiro Ritonga (CV. Multi Kreasi Media, 2025)
Community empowerment aims to improve the ability of individuals and groups to utilize social, economic, and political circumstances. Strategic steps in the process seek to increase knowledge, develop skills, provide access to resources and technology, and provide moral support. This concept emerged as a critique of previous development approaches that overemphasized economic growth without regard for equitable distribution of social benefits. The ongoing development inequality in various regions of Indonesia demands the formulation of empowerment programs that are more contextual, participatory, and based on community needs. This study uses a Systematic Literature Review (SLR) approach with the SALSA (Search, Appraisal, Synthesis, and Analysis) framework to identify factors, variables, and indicators that impact community welfare. The literature analyzed was selected from scientific publications during the 2020–2024 period, with a focus on studies relevant to community welfare in Indonesia. Selected articles were analyzed to obtain substantive findings. The results indicate that community welfare is influenced by unemployment rates, household income, access to education, quality of health services, residential environmental conditions, financial behavior, and the use of information technology. The conclusion of this study confirms that community empowerment activities must be designed with proven relevant indicators and the socioeconomic characteristics of the target area in mind. Empowerment programs aimed at job creation, skills development, access to basic services, and strengthening local institutions are more likely to promote sustainable prosperity. The key to creating an inclusive and impactful empowerment program lies in synergy among stakeholders.